Political institutions, human capital and innovation: evidence from sub-Saharan Africa. Issue 4 (19th May 2019) - Bekana, Dejene Mamo
ABSTRACT: Using data for a sample of 35 sub-Saharan African economies for 1995–2015, this study examines the extent to which political institutions identified as belonging to democratic or autocratic regimes explains the existing differences in innovation across sub-Saharan Africa. While the very few existing studies focus only on the direct effect of institutions, this article examines the impact of the interaction between different regime types and human capital development on innovation in developing countries. The evidence provides very strong support for the direct effect of democratic development on innovation as well as for its indirect effect via its impact on human capital development. However, the results do not support theories that argue in favour of interaction between democracy and human capital, thereby pointing to the need for better calibration of the numerous existing theories and related empirical measures.